Application of a fuzzy set theory for supplier’s selection - Куимова, Елена Ивановна; Логанина, Валентина Ивановна; Учаева, Татьяна Владимировна (Eastern-European Journal of Enterprise Technologies, 2013)
The paper gives information on methods of supplier’s selection assessment based on the fuzzy set theory. The decision-making algorithm is presented. The concrete example is cited concerning cement supplier’s selection for one of the construction enterprises in Penza when producing reinforced concrete. The supplier’s criteria were price, quality of supplied raw materials, available free space for power increase and reliability. For estimating the weight coefficient values, matrix of pairwise criteria comparisons was formulated. Matrix of multiplicative quantitative assessments was made. A set of optimal alternatives taking into account the weight of various quality criteria was determined using the weighted intersection of fuzzy sets. The weight coefficients of criteria were determined based on calculated values of the right eigenvector matrix of pairwise comparisons with further multiplying by the number of criteria. The calculation results of the weight coefficients of supplier’s criteria are presented.